2018
DOI: 10.1159/000489979
|View full text |Cite
|
Sign up to set email alerts
|

Novel Therapeutic Strategies for Solid Tumor Based on Body’s Intrinsic Antitumor Immune System

Abstract: The accumulation of mutated somatic cells due to the incompetency of body’s immune system may lead to tumor onset. Therefore, enhancing the ability of the system to eliminate such cells should be the core of tumor therapy. The intrinsic antitumor immunity is triggered by tumor-specific antigens (TSA) or TSA-sensitized dendritic cells (DC). Once initiated, specific anti-tumor antibodies are produced and tumor-specific killer immune cells, including cytotoxic T lymphocytes (CTL), NK cells, and macrophages, are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Our study also confirmed the changes in cochlear ribbon synapse morphology and number before hearing maturation. Macrophages are one of the key elements of the intrinsic immune system in mature organs, and they primarily function as an immunological defense to keep the internal environment at homeostasis ( Wynn and Vannella, 2016 ; Duan, 2018 ), and macrophages are resident immune cells in the cochlea ( Liu et al, 2018 ; He et al, 2020 ). They play a continuous monitoring role in the homeostatic environment, thus helping maintain tissue homeostasis under pathological and physiological conditions ( Ito et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also confirmed the changes in cochlear ribbon synapse morphology and number before hearing maturation. Macrophages are one of the key elements of the intrinsic immune system in mature organs, and they primarily function as an immunological defense to keep the internal environment at homeostasis ( Wynn and Vannella, 2016 ; Duan, 2018 ), and macrophages are resident immune cells in the cochlea ( Liu et al, 2018 ; He et al, 2020 ). They play a continuous monitoring role in the homeostatic environment, thus helping maintain tissue homeostasis under pathological and physiological conditions ( Ito et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxic environment caused by rapid growth also produces reactive oxygen species. The oxidative stress and metabolic disturbances, in turn, promote a chronic inflammatory environment 3 . This hypoxic and chronically inflamed environment, combined with persistent antigenic stimulation in the tumor, changes T cell activity: cells previously poised for a cytotoxic response become exhausted and convert to support cells that aid in the post-cytotoxic repair response, further benefiting tumor growth.…”
Section: Main Textmentioning
confidence: 99%
“…Immunotherapy is extremely important in antitumor response and the immune system is enhanced by activating immune cells (Duan, 2018). Most invaders can be killed by the immune system of the organism but some tumor cells may maintain antigenicity and immunogenicity to evade recognition by tumor‐specific T cells, which called “immune evasion” (Beatty & Gladney, 2015).…”
Section: Introductionmentioning
confidence: 99%